2020
DOI: 10.1182/blood.2020006321
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4 is Regulated by HIF and Mediates Mobilization of Murine Hepatic Iron Stores After Blood Loss

Abstract: The mechanisms by which phlebotomy promotes the mobilization of hepatic iron stores are not well understood. NCOA4 (nuclear receptor coactivator 4) is a widely-expressed intracellular protein previously shown to mediate the autophagic degradation of ferritin. Here, we investigate a local requirement for NCOA4 in the regulation of hepatic iron stores and examine mechanisms of NCOA4 regulation. Hepatocyte-targeted Ncoa4 knockdown in non-phlebotomized mice had only modest effects on hepatic ferritin subunit level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 63 publications
2
34
1
Order By: Relevance
“…Subsequent NCOA4 promoter activity analysis in human intestinal cell lines established that intestinal NCOA4 is a specifically dependent on HIF-2α. In contrast to a recent report, where it was demonstrated that hepatic NCOA4 is a target of both HIF-1α and HIF-2α, we show that intestinal NCOA4 expression is specifically dependent on HIF-2α, but not on HIF-1α (17). This exemplifies that ferritinophagy is differentially regulated across different tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…Subsequent NCOA4 promoter activity analysis in human intestinal cell lines established that intestinal NCOA4 is a specifically dependent on HIF-2α. In contrast to a recent report, where it was demonstrated that hepatic NCOA4 is a target of both HIF-1α and HIF-2α, we show that intestinal NCOA4 expression is specifically dependent on HIF-2α, but not on HIF-1α (17). This exemplifies that ferritinophagy is differentially regulated across different tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study showed that hepatocyte-specific expression of NCOA4, the protein that directs ferritin to autophagosomes and lysososomes, is required for erythropoiesis [65]. Obviously, in order to be used by the erythron, iron must exit the liver; therefore, it can be inferred that FPN expression in hepatocytes is also necessary for a prompt iron mobilization in response to increased demand.…”
Section: Livermentioning
confidence: 99%
“…NCOA4 specifically binds ferritin and delivers it to lysosomes where it is degraded, thereby increasing iron availability [ 29 ]. This mechanism, which is controlled by iron and oxygen levels through hypoxia inducible factors [ 30 ], may be beneficial in macrophages where it is accompanied by iron release, as it would sustain erythropoiesis, particularly under conditions of iron deficiency [ 31 ].…”
Section: Iron Handling By Macrophagesmentioning
confidence: 99%